Odpowiedzi

2010-03-01T18:05:39+01:00
A) 3-2x=-5x+6
-2x+5x=6-3
3x=3
1x=1
Najlepsza Odpowiedź!
2010-03-01T18:06:22+01:00
A) 3-2x=-5x+6
-2x+5x = 6-3
3x = 3 / : 3
x = 1

b) 5x+2-4(2x-1)≥ -3
5x+2-8x+4 ≥ -3
5x-8x ≥-3-2-4
-3x ≥ -9 / : (-3)
x ≤ 3
rozwiązaniem jest zbiór (-∞ ; 3>

c)x-3 w mianowniku 2 ≥-1 / * 2
x-3 ≥ -1 *2
x-3 ≥-2
x ≥ -2+3
x ≥ 1
rozwiązaniem jest zbiór <1 ; +∞)

d x-3 w mianowniku 2 < x+1 w mianowniku 3 / * 6
3 (x-3) < 2 (x+1)
3x-9 < 2x+2
3x-2x < 2+9
x < 11
rozwiązaniem jest zbiór (-∞ ; 11)